Hukum Kristus di Era Krisis Ekologi: Mengintegrasikan Pemikiran Bernhard Haring dengan Ekologi Integral dalam Laudato Si - Fofid, Elisabet Maria; Irawan, Paulus Bambang (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
The recent climate change is one of the consequences of the gap in the relationship between humans and the universe. This gap ultimately gives rise to a prolonged ecological crisis. The current environmental crisis is a global challenge, with severe impacts such as increased migration, loss of homes, and the extinction of various plant and animal species. Conditions like these are essentially caused by the loss of human connectivity and sensitivity to nature, which then leads to unpredictable weather changes, decreased agricultural yields, and the exploitation of environmental issues in political policies. In response to this crisis, this paper proposes an integration between the concept of the Law of Christ from Bernhard Haring's thought and the idea of integral ecology in Laudato Si by Pope Francis. So the question of this paper is how to rebuild human connectivity and sensitivity to nature through responsible moral action. The method of this paper is to analyze the concept of the law of Christ according to Bernhard Haring and integrate it with the understanding of the integral ecology of Pope Francis in the encyclical Laudato Si. Bernhard Haring, who lived during World War II, emphasized love as the core of the Law of Christ, where love encourages responsible moral action towards others and nature. He also underlines the importance of freedom of action balanced with responsibility for its impact on creation. Meanwhile, Pope Francis in Laudato Si sees the roots of the ecological crisis in technology, the technocratic paradigm, and the modern anthropocentric view. Pope Francis offers the principle of solidarity and the importance of considering the impact of our actions on the environment for future generations. Both of these thoughts emphasize the need for an ecological conversion based on love as the main driver to give birth to awareness of the importance of responsible moral action to recreate the harmony of the relationship between humans and the universe as a common home.AbstrakPerubahan iklim yang terjadi akhir-akhir ini merupakan salah satu akibat dari  adanya kesenjangan relasi antara manusia dan alam semesta. Kesenjangan ini pada akhirnya melahirkan krisis ekologi yang berkepanjangan. Krisis ekologi saat ini menjadi tantangan global, dengan dampaknya yang sangat serius seperti meningkatnya migrasi, hilangnya tempat tinggal, serta punahnya berbagai spesies tumbuhan dan hewan. Kondisi-kondisi seperti ini pada hakekatnya disebabkan oleh hilangnya konektivitas dan sensitivitas manusia terhadap alam, yang kemudian berujung pada perubahan cuaca tidak menentu, penurunan hasil pertanian, dan eksploitasi isu lingkungan dalam kebijakan politik. Menanggapi krisis ini, paper ini mengusulkan integrasi antara konsep Hukum Kristus dari pemikiran Bernhard Haring dan konsep ekologi integral dalam Laudato Si oleh Paus Fransiskus. Maka pertanyaan dari paper ini adalah bagaimana membangun kembali konektivitas dan sensivitas manusia dengan alam melalui tindakan moral yang bertanggungjawab? Metode dari paper ini adalah menganalisa konsep hukum Kristus menurut Bernhard Haring dan mengintegrasikannya dengan paham ekologi integral Paus Fransiskus dalam ensiklik Laudato Si. Bernhard Haring, yang hidup di masa Perang Dunia II, menekankan kasih sebagai inti Hukum Kristus, di mana kasih mendorong tindakan moral yang bertanggungjawab terhadap sesama dan alam. Ia juga menggarisbawahi pentingnya kebebasan untuk bertindak yang diimbangi dengan tanggung jawab atas dampaknya terhadap ciptaan. Sementara itu, Paus Fransiskus dalam Laudato Si melihat akar dari krisis ekologi adalah teknologi, paradigma teknokratis dan pandangan antroposentrisme modern. Paus Fransiskus menawarkan prinsip solidaritas dan pentingnya mempertimbangkan dampak tindakan kita terhadap lingkungan untuk generasi mendatang. Kedua pemikiran ini menekankan perlunya pertobatan ekologis yang berdasarkan pada kasih sebagai penggerak utama untuk melahirkan kesadaran akan pentingnya tindakan moral yang bertanggung jawab untuk menciptakan kembali harmonisasi relasi antara manusia dan alam semesta sebagai rumah bersama.